Puberphonia: From classic to modern approach - Bojana Vuković; Sladjana Ćalasan (Биомедицинска истраживања, 2021)
Voice is a significant component of communication that allows us to express information and emotions, so it is the foundation of verbal communication. Maturation of the body involves dilation of the larynx and lower positioning of the larynx in the neck, resulting in multiple changes in voice quality. The rapid changes in the human larynx during puberty are more evident in males. Such changes can result in voice mutation - puberphonia. Puberphonia, also called mutational dysphonia or mutational falsetto, is the failure of a natural decrease in fundamental frequency or pitch. We can also defined puberphonia as persistent adolescent voice even after puberty in the absence of organic cause. This functional voice disorder can have multiple consequences on the personality and quality of life of an individual that often encounters problems that include psychological, emotional, social, and professional difficulties. This article aims to Reviews the relevant and accessible literature on puberphonia in a comprehensive concise manner, highlighting the etiology, prevalence, clinical manifestation, consequences on quality of life, as well as evolution of the approach and attitude to its treatment.
Keywords: voice mutation; puberty; puberphonia